Vascular Tissue Engineering: Polymers and Methodologies for Small Caliber Vascular Grafts - Leal, Bruna B. J.; Wakabayashi, Naohiro; Oyama, Kyohei; Kamiya, Hiroyuki; Braghirolli, Daikelly I.; Pranke, Patricia (Frontiers in Cardiovascular Medicine, 2021)
Cardiovascular diseases are the cause of most deaths in the world. They can provoke damage to blood vessels, such as stenosis, dilation or occlusion, causing difficulty in the blood flow. This damage can be treated with medication, vasodilators or anticoagulants in less severe cases. When these drugs are not effective, autologous vascular grafts are a treatment option. Autologous grafts are the gold standard, however, they have some limitations in quantity and quality of the native blood vessel. In these cases, synthetic vascular grafts are used. There are currently several vascular grafts which have been developed and with excellent results for application in medium and large caliber vessels, such as Dacron. In relation to small caliber synthetic grafts (<5 mm), there is greater difficulty for development as these grafts have a high failure rate, mainly due to thrombus formation and intimal hyperplasia inside the graft. They can be developed using methodologies available in vascular tissue engineering, such as electrospinning, decellularization, lyophilization and 3D printing. The polymers used for the development of vascular grafts are natural ones, such as collagen and chitosan, or synthetic polymers, such as PCL and PLCL. This review article includes topics on the methodologies used in the development of vascular grafts and the polymers used in vitro and vivo.